Management of Filamentous Fungal Keratitis: A Pragmatic Approach - Hoffman, Jeremy J.; Arunga, Simon; Ahmed, Abeer H. A. Mohamed; Hu, Victor H.; Burton, Matthew J. (Journal of Fungi, 2022)
Filamentous fungal infections of the cornea known as ﬁlamentous fungal keratitis (FK) are challenging to treat. Topical natamycin 5% is usually ﬁrst-line treatment following the results of several landmark clinical trials. However, even when treated intensively, infections may progress to corneal perforation. Current topical antifungals are not always effective and are often unavailable. Alternatives topical therapies to natamycin include voriconazole, chlorhexidine, amphotericin B and econazole. Surgical therapy, typically in the form of therapeutic penetrating keratoplasty, may be required for severe cases or following corneal perforation. Alternative treatment strategies such as intrastromal or intracameral injections of antifungals may be used. However, there is often no clear treatment strategy and the evidence to guide therapy is often lacking. This review describes the differenttreatmentoptionsandtheirevidenceandprovidesapragmaticapproachtothemanagement of fungal keratitis, particularly for clinicians working in tropical, low-resource settings where fungal keratitis is most prevalent.
Keywords: Microbial keratitis; Fungal keratitis; Management; Antifungals; Microbiology; Natamycin; Chlorhexidine